Barcas de Ubaid: navegaciones predinásticas en el Golfo Pérsico - Guerrero Ayuso, Víctor M. (Complutum, 2007)
Pre-dynastic communities in Lower Mesopotamia did not produce such abundant or so detailed iconographic work as the Egyptians. This no doubt explains why their seafaring capacity has not been fairly assessed in written history. Recent iconographic and archaeological finds corresponding to the Ubaid culture have clearly demonstrated that sea voyages to Qatar and Dubai were a well-established fact in the mid 6th millennium cal. BC. In this paper, a review is made of all documentation relative to the nautical activities of the Ubaid people, pointing out that all categories of boats (reed boats and guffas) had been fully developed by this period.